La dislexia y su incidencia en el desarrollo emocional en los estudiantes de la Unidad Educativa Delia Ibarra de Velasco periodo 2019 - Rodríguez Acosta, Madeline Adriana (2019)
Dyslexia is a learning problem that mainly affects children, detected from the school stage, it is there where this problem is observed, since the child begins his learning process in reading and writing; It is worth mentioning that children, adolescents and young people who have this difficulty have a normal intelligence, this disorder is focused even more at the neurological level, so it is very important to carry out the studies and / or examinations for the problem Learning. The objective of this research is to identify the components of emotional intelligence that are most frequently affected in children with dyslexia. The study was of descriptive type of non-experimental and transversal design. We worked with a universe of 375 students in the section of the degrees of the Educational Unit Delia Ibarra De Velasco del Canton Quevedoqw St. Camilo parish. A Psychometric Test was applied to the universe to detect students who manifest dyslexia problems. Once identified, this group was only assigned a test to measure their emotional intelligence and thus prove that it affects students in their development at a level Social. So the components of emotional intelligence that are most often affected in children with dyslexia are: self-control, self-awareness and empathy. That is why it is necessary to look for strategies or techniques that help children to control their emotions, to detach them from negative emotion focusing their attention on neutral or positive thoughts, this help can be at the psychological level so that the results are optimal in each one of them.